Towards critical global education worker subjectivity: An exploration of narratives of American women engaged in education-related international volunteerism (International Journal of Development Education and Global Learning, 2017)
International volunteerism is increasingly associated with shaping global subjectivities of participants. Significant numbers of Global North volunteers – whether working through established volunteer organizations, corporations, nonprofits, academia, or personal networks and connections – engage in educationrelated activities while in the Global South. I emphasize in this paper that education-related international volunteering presents a rich context in which to explore global subjectivities due to the high likelihood of participants' engagement with mobility, difference, poverty, inequality, and development. In this paper, I explore six women's accounts of their transnational experiences and resulting understandings of their education-related work. Four related thematic categories derived from these accounts convey meanings of education-related work in terms of self-fulfilment, social responsibility, active engagement with host communities, and cross-cultural competence. I explore two overlapping subjectivities – participatory and critical – that emerge from an exploration of these themes, examine how they intersect with common discourses of international volunteering and development, and discuss the implications for the relationship between global citizenship and education-related international volunteering.